Designing a programming mobile application for novice users: a prototype / Azlina Mohd Mydin, Wan Anisha Wan Mohammad, Syarifah Adilah Mohamed Yusoff - Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha; Mohamed Yusoff, Syarifah Adilah (UiTM Press, 2020)
Mobile application or mobile apps has been a trending technology nowadays. This can lead to a new way of learning style. Learning process also becomes easier with the over-increasing development of education mobile apps. Novice programmers can learn programming easily with the development of programming mobile apps. A good programming mobile apps should not only focus on delivering the content but also on various aspect such as availability, usability, dependability, performance and functionality. Thus, a prototype on programming mobile apps has been designed to cater the needs of novice users. This paper will study the suitable method on system development that focus on activities and content arrangements based on the survey that has been done prior to the design. From the method chosen, a full system layout will be designed as a preliminary process before developing an effective programming mobile application.